Amygdala abnormalities across disease stages in patients with sporadic amyotrophic lateral sclerosis. Issue 18 (22nd July 2022) - Liu, Shuangwu; Zhao, Yuying; Ren, Qingguo; Zhang, Dong; Shao, Kai; Lin, Pengfei; Yuan, Ying; Dai, Tingjun; Zhang, Yongqing; Li, Ling; Li, Wei; Shan, Peiyan; et al.
Abstract: To examine selective atrophy patterns and resting‐state functional connectivity (FC) alterations in the amygdala at different stages of amyotrophic lateral sclerosis (ALS), and to explore any correlations between amygdala abnormalities and neuropsychiatric symptoms. We used the King's clinical staging system for ALS to divide 83 consecutive patients with ALS into comparable subgroups at different disease stages. We explored the pattern of selective amygdala subnucleus atrophy and amygdala‐based whole‐brain FC alteration in these patients and 94 healthy controls (HCs). Cognitive and emotional functions were also evaluated using a neuropsychological test battery. There were no significant differences between ALS patients at King's stage 1 and HCs for any amygdala subnucleus volumes. Compared with HCs, ALS patients at King's stage 2 had significantly lower left accessory basal nucleus and cortico‐amygdaloid transition volumes. Furthermore, ALS patients at King's stage 3 demonstrated significant reductions in most amygdala subnucleus volumes and global amygdala volumes compared with HCs. Notably, amygdala‐cuneus FC was increased in ALS patients at King's stage 3. Specific subnucleus volumes were significantly associated with Mini‐Mental State Examination scores and Hamilton Anxiety Rating Scale scores in ALS patients. In conclusions, our study provides a comprehensive profile of amygdala abnormalities in ALS patients. The pattern of amygdala abnormalities in ALS patients differed greatly across King's clinical disease stages, and amygdala abnormalities are an important feature of patients with ALS at relatively advanced stages. Moreover, our findings suggest that amygdala volume may play an important role in anxiety and cognitive dysfunction in ALS patients. Abstract : Our study provides a comprehensive profile of amygdala abnormalities in ALS patients. The pattern of amygdala abnormalities in ALS patients differed greatly across King's clinical disease stages, and amygdala abnormalities are an important feature of patients with ALS at relatively advanced stages. Moreover, amygdala may play an important role in anxiety and cognitive dysfunction in ALS patients.